2004
DOI: 10.1073/pnas.0400593101
|View full text |Cite
|
Sign up to set email alerts
|

Silent information regulator 2 potentiates Foxo1-mediated transcription through its deacetylase activity

Abstract: Longevity regulatory genes include the Forkhead transcription factor FOXO and the NAD-dependent histone deacetylase silent information regulator 2 (Sir2). Genetic studies demonstrate that Sir2 acts to extend lifespan in Caenorhabditis elegans upstream of DAF-16, a member of the FOXO family, in the insulin-like signaling pathway. However, the molecular mechanisms underlying the requirement of DAF-16 activity in Sir2-mediated longevity remain unknown. Here we show that reversible acetylation of Foxo1 (also known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
452
2
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 538 publications
(482 citation statements)
references
References 47 publications
20
452
2
1
Order By: Relevance
“…Fukuoka et al (2003) reported that acetyl transferase CBP suppresses FOXO4 through acetylation, whereas Perrot and Rechler (2005) found that p300 acetylates FOXO1 and stimulates FOXO1-induced transcription. Similarly controversial are the effects of FOXO deacetylation by sirtuins, with reports of either increase or decrease of the expression of FOXO target genes (Brunet et al, 2004;Daitoku et al, 2004;Motta et al, 2004;van der Horst et al, 2004;Yang et al, 2005). So far, however, the data are consistent regarding the effect of FOXO deacetylation on FOXO DNA-binding to targeting gene promoters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fukuoka et al (2003) reported that acetyl transferase CBP suppresses FOXO4 through acetylation, whereas Perrot and Rechler (2005) found that p300 acetylates FOXO1 and stimulates FOXO1-induced transcription. Similarly controversial are the effects of FOXO deacetylation by sirtuins, with reports of either increase or decrease of the expression of FOXO target genes (Brunet et al, 2004;Daitoku et al, 2004;Motta et al, 2004;van der Horst et al, 2004;Yang et al, 2005). So far, however, the data are consistent regarding the effect of FOXO deacetylation on FOXO DNA-binding to targeting gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Caloric restriction stimulates the expression of both SIRT1 and SIRT2 (Cohen et al, 2004;Wang et al, 2007). SIRT1 regulates many cellular processes through deacetylation of various substrates (Verdin, 2007), including FOXO1, FOXO3 and FOXO4 (Brunet et al, 2004;Daitoku et al, 2004;Motta et al, 2004;van der Horst et al, 2004;Yang et al, 2005). The dysregulation of SIRT1 expression and activity is closely related to tumorigenesis (Kabra et al, 2009;Liu et al, 2009;Sung et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, whereas antioxidant defense mechanisms are prominent in aerobic tissues such as retina and brain, cross-species comparisons show that they are either uncorrelated or negatively correlated with LSP 18 . Transgenic overexpression of antioxidant enzymes, such as superoxide dismutase, can have large effects on lifespan [35][36][37] , but naturally occurring antioxidant defenses do not readily account for differences in LSP 18 .…”
Section: Interpreting Allometric Differencesmentioning
confidence: 99%
“…Both caloric restriction and many of these mutants use a common pathway involving SIRT protein deacetylases and the forkhead transcription factor family (FOXO or Daf-16), which can upregulate mitochondrial Sod2 and other antioxidant defenses and reduce apoptotic cell death 36,37 . Antioxidant defenses are therefore important influences on both cell death and longevity, but evolution seems to have favored limiting RONS production rather than increasing their destruction 18 , perhaps because RONS also have cellular signaling roles.…”
Section: Interpreting Allometric Differencesmentioning
confidence: 99%